Sustainable Entrepreneurship and Community Empowerment: Case Study at PT. Semen Tonasa - Multhazam, Riana; Tawe, Amiruddin; Rakib, Muhammad; Sulolipu, Andi Annisa (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
The purpose of this study is to analyze sustainable entrepreneurship practices implemented by PT. Semen Tonasa, including an assessment of the programs that have been implemented, as well as innovations applied in the process and management of resources. And also aims to analyze the impact of community empowerment programs carried out by the company. This study will explore how these programs affect community welfare, both economically and socially, and to provide recommendations that can be used by PT. Semen Tonasa in developing effective empowerment programs in the future by identifying existing challenges and opportunities, it is hoped that the company can continue to contribute to sustainable development in the community. This study uses a qualitative approach with a case study design. The results of the study indicate that PT. Semen Tonasa has succeeded in implementing sustainable entrepreneurship practices that have a positive impact on community empowerment. The programs implemented not only improve community skills but also create new jobs and reduce environmental impacts. However, there are still challenges that need to be overcome so that these programs can run more effectively.